Effect of Fortification of Anchovy Flour on Calcium Content, Orgnoleptic Quality and Shelf Life of Canned Tuna Porridge Products - Tangke, Umar; Talib, Ahmad; Daeng, Ruslan A (Agrikan Jurnal Agribisnis Perikanan, 2022)
This research was conducted with the aim of knowing the effect of anchovy meal fortification on organoleptic quality and determining the best product based on a completely randomized design and Bayes method. The results showed that based on the results of the analysis using the Bayes method, canned tuna porridge with 3% anchovy flour fortification (A1 treatment) was the best product with a weight of 4.00 tilapia, followed by treatments A0 and A2 with a weighted value of 3.23 each. and 2.62.